2022
DOI: 10.1093/ije/dyac031
|View full text |Cite
|
Sign up to set email alerts
|

Opium use and risk of bladder cancer: a multi-centre case-referent study in Iran

Abstract: Background Bladder cancer (BC) is the 10th most common type of cancer worldwide and the fourth most common type of cancer in Iran. Opium use is considered as one of the risk factors for BC. We aim to assess the association between various parameters of opium use, which in Iran is mainly ingested or smoked in various forms, and the risk of BC. Method In this multi-centre case-referent study in Iran, 717 BC cases and 3477 refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Cumulative exposure information was available for some studies of cancers of the urinary bladder [8,30,31,43], larynx [8,32], lung [8,33,34], pancreas [8,35,36] and stomach [8,37,55] (never versus ≤ median and > median use). Estimates of association between ≤ median and > median of cumulative opium exposure compared to never use for various cancers in the GCS [8], and for bladder cancer in the IROPICAN study [38] were obtained through personal communication with the study authors (November 2021, and April 2022, respectively). The models included adjustment for age, sex, and tobacco smoking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cumulative exposure information was available for some studies of cancers of the urinary bladder [8,30,31,43], larynx [8,32], lung [8,33,34], pancreas [8,35,36] and stomach [8,37,55] (never versus ≤ median and > median use). Estimates of association between ≤ median and > median of cumulative opium exposure compared to never use for various cancers in the GCS [8], and for bladder cancer in the IROPICAN study [38] were obtained through personal communication with the study authors (November 2021, and April 2022, respectively). The models included adjustment for age, sex, and tobacco smoking.…”
Section: Discussionmentioning
confidence: 99%
“…There were 2 prospective cohort studies and 33 case-control studies. There were a total of six new case-control studies identified following the Monographs meeting [30,35,38,[42][43][44]. A total of 15 studies examined the association between opium consumption and bladder cancer (1 cohort and 14 case-control), 7 for laryngeal cancer (1 cohort and 6 case-control), 6 for oesophageal cancer (1 cohort and 4 case-control, one publication [41] describes two separate studies, with different sets of cases and controls), 5 for stomach cancer (2 cohort and 3 case-control), 5 for lung cancer (1 cohort and 4 case-control), and 4 for pancreatic cancer (1 cohort and 3 case-control).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Adjustment for opium consumption, which has been recently classified as a human carcinogen, (including for urinary bladder cancer) by the IARC monograph programme, 13 is also important because over 40% of the world's opium use takes place in Iran 34 . The latest study, based on data from the IROPICAN study, shows that the adjusted risk of bladder cancer associated with ever opium consumption is 3.5 (CI: 2.8, 4.3) 35 . After adjustment for this risk factor, the risk of bladder cancer may be significantly affected.…”
Section: Discussionmentioning
confidence: 99%